3-D reservoir characterization and hydrocarbon volumetric estimation of parts of Niger Delta Basin-Nigeria. (August 2021) - Ebong, Ebong D.; Akpan, Anthony E.; Ekwok, Stephen E.; Esu, Esu O.; Ebong, Loveth A.
Abstract: Coupled interpretation and modeling of seismic and well log data, using geostatistical techniques was adopted to characterize reservoirs in a section of the Niger Delta Basin. The study was aimed at generating high resolution reservoir information such as spatial distribution of petrophysical properties, subsurface structures (e.g., faults and horizons) and estimation of hydrocarbon volume in a heterogeneous reservoir system. Five reservoirs with over twenty fault structures were delineated. The reservoir structural framework consists of antithetic and synthetic faults that influenced hydrocarbon flow dynamics within the field. Petrophysical properties were estimated and spatially distributed over the study area via variogram statistics. Both the sequential indicator and Gaussian simulations were performed to transform the pillar grids during the modeling process. Three realizations of the volumetrics were obtained for each of the reservoirs and the overall stock tank oil initially in place of the field, show low outcome of 245, 720, 570.40 stock tank barrels (STB) which indicates 90% probability of exceeding the quoted value, median outcome of 302, 735, 521.90 STB called the reality-oriented model (i.e., 50% probability) and a high outcome of 361, 161, 605.40 STB which has 10% probability of exceeding the estimated value. The gas zone estimate show low, median and high outcomes of 53, 745.50, 56, 487.60 and 60, 618.50 million standard cubic feet (mmscf) respectively. Generally, results obtained show that an integration of well log and seismic data using geostatistical techniques can yield geological plausible reservoir models that can enhance production and management decisions in complex heterogeneous reservoir systems. Highlights: Seismics and well logs were integrated via geostatistical techniques to characterize reservoirs. Horizons and fault structural framework were interpreted. Petrophysical properties were evaluated and spatially distributed over 3D grid. Equiprobable realizations of hydrocarbon volume and uncertainties were achieved. The study provides a reliable volumetric estimation that can enhance management decisions.